Análisis y estructuración de las creencias que tienen sobre la matemática estudiantes de básica secundaria del liceo femenino mercedes Nariño - Sánchez Cruz, Maryi Alexandra (Universidad Antonio Nariño, 2023)
The objective of this work was to describe the beliefs about the mathematics of a group of twelve students of IED Liceo Femenino Mercedes Nariño, a public school in the city of Bogotá, belonging to the eighth, ninth and tenth grades, and to deepen on the way they have been educated.